The dual role of the gut microbiota in breast cancer: from pathogenic mechanisms to emerging therapeutic - Zhao, Yihong; Zhao, Ye; Shi, Jingyi; Guan, Bingrui; Long, Meihan; Sun, Zhenzhen; Jin, Shanlin; Ye, Yan; Chang, Tiebao; Fu, Yunhe; Zheng, Huihua; Xie, Guanghong (Frontiers in Microbiology, 2025)
Recent studies indicate that breast cancer (BC) has surpassed lung cancer as the most frequently diagnosed cancer worldwide and remains the leading cause of cancer-related death among women. Although advances in medical therapy have improved survival rates for BC patients, its etiology is highly complex and necessitates further investigation into the underlying biological mechanisms and risk factors. The gut microbiota, a critical microbial ecosystem within the human body, is increasingly recognized as being closely linked to the initiation and progression of various diseases, including BC. It plays a pivotal role in key physiological processes such as estrogen metabolism and immune regulation. Gut microbiota dysbiosis may contribute to pathological alterations that influence BC development, progression, and response to treatment. This review summarizes the current understanding of the gut microbiota’s role in BC pathogenesis and therapeutic outcomes, highlighting recent advances. We discuss the mechanistic pathways by which the gut microbiota affects BC, including modulation of estrogen metabolism, immune system regulation, and impacts on treatment efficacy, thereby providing a theoretical framework for further exploration of disease mechanisms and therapeutic interventions. Moreover, by synthesizing and critically analyzing existing evidence, this review identifies emerging research directions and potential therapeutic targets, offering valuable insights for future translational research and clinical applications.